Inhibition of prolyl hydroxylase domain proteins selectively enhances venous thrombus neovascularisation. Issue 169 (September 2018) - Grover, S.P.; Saha, P.; Humphries, J.; Lyons, O.T.; Patel, A.S.; Serneels, J.; Modarai, B.; Mazzone, M.; Smith, A.
Abstract: Background: Hypoxia within acute venous thrombi is thought to drive resolution through stabilisation of hypoxia inducible factor 1 alpha (HIF1α). Prolyl hydroxylase domain (PHD) isoforms are critical regulators of HIF1α stability. Non-selective inhibition of PHD isoforms with l-mimosine has been shown to increase HIF1α stabilisation and promote thrombus resolution. Objective: The aim of this study was to investigate the therapeutic potential of PHD inhibition in venous thrombus resolution. Methods: Thrombosis was induced in the inferior vena cava of mice using a combination of flow restriction and endothelial activation. Gene and protein expression of PHD isoforms in the resolving thrombus was measured by RT-PCR and immunohistochemistry. Thrombus resolution was quantified in mice treated with pan PHD inhibitors AKB-4924 and JNJ-42041935 or inducible all-cell Phd2 knockouts by micro-computed tomography, 3D high frequency ultrasound or endpoint histology. Results: Resolving venous thrombi demonstrated significant temporal gene expression profiles for PHD2 and PHD3 (P < 0.05), but not for PHD1. PHD isoform protein expression was localised to early and late inflammatory cell infiltrates. Treatment with selective pan PHD inhibitors, AKB-4924 and JNJ-42041935, enhanced thrombus neovascularisation (P < 0.05), but had no significant effect on overall thrombus resolution. Thrombus resolution or its markers, macrophage accumulation and neovascularisation, did not differ significantly in inducible all-cell homozygous Phd2 knockouts compared with littermate controls (P > 0.05). Conclusions: This data suggests that PHD-mediated thrombus neovascularisation has a limited role in the resolution of venous thrombi. Directly targeting angiogenesis alone may not be a viable therapeutic strategy to enhance venous thrombus resolution. Highlights: Tissue hypoxia is thought to be a critical driver of venous thrombus resolution. Prolyl hydroxylase domain proteins (PHDs) are critical oxygen sensors. Broad pharmacological PHD inhibition selectively enhances neovascularisation. Thrombus neovascularisation and resolution occur independent of Phd2 gene deletion.